Slope stability analysis and rehabilitation for finite slope - Wan Muhammad Shazwan Bin Wan Shuhaimi (School of Environmental Engineering, University Malaysia Perlis, 2014)
This study was conducted to analyse the safety factor of the slope at Bukit Mengkuang , Jitra . This study involves the collection of soil sample and the soil properties will be obtained from laboratory test. Then, the simulation for the slope by using Plaxis 2D software will be analysed. From the analysis on the slope, soil type, slope safety factor, shear strain and slope repair can be determined. This study also includes simulations some rehabilitation method on the slope to avoid the slope of failure. The effectiveness of a rehabilitation method slope for slope stability is a very important factor to prevent slope failure occurs.